Sedimentology and Geochemistry of the Lower Permian Shanxi Formation Shan 23 Submember Transitional Shale, Eastern Ordos Basin, North China - Gu, Yifan; Li, Xingtao; Qi, Lin; Li, Shuxin; Jiang, Yuqiang; Fu, Yonghong; Yang, Xiaoshuai (Frontiers in Earth Science, 2022)
Shanxi Formation Shan 23 Submember transitional shale in Eastern Ordos Basin is characterized by high TOC value, wide distribution, and large single-layer/cumulative thickness. In this study, based on section division of Shan 23 Submember, petrographic, mineralogical, and high-resolution geochemical analyses were integrated to reveal sedimentary environment, detrital influx, paleoclimate, paleosalinity, and paleoredox conditions. Results indicate that Shan 23 Submember is divided into four sections (Shan 23-1, Shan 23-2, Shan 23-3, and Shan 23-4). The upper part of the Shan 23-1 section is dominated by bay facies, which is characterized by high TOC value (2.75%–10.96%, avg. 6.98%), low detrital influx proxies (Zr, 97–527 ppm, avg. 310 ppm; Ti, 1985–7591 ppm, avg. 3938 ppm), relatively dry paleoclimate condition (CIA*, 41.96–92.58, avg. 75.55; Sr/Cu, 6.23–14.49, avg. 8.87), high paleosalinity proxies (Sr/Ba, 0.39–1.29, avg. 0.62), and relatively anoxic reduction condition (UEF, 0.83–3.00, avg. 1.67; MoEF, 3.95–27.00, avg. 15.56). By comparison, the other three sections are dominated by a combination of transitional facies, including barrier island, lagoon, tidal flat, and swamp. In this interval, shale is deposited in lagoon facies. The paleoclimate gradually tends to be warm and humid, which results in increasing the chemical weathering intensity. Meanwhile, the detrital influx increases, and the paleoredox condition tends to be oxic. The above conditions are not conducive to the preservation of organic matter in lagoon facies shale.